The role of trait mindfulness, self-compassion, and caring for bliss in life satisfaction: Controlling for perceived stress during the COVID-19 pandemic - Aydın Sünbül, Zeynep; Çekici, Ferah (Slovak Academy, 2023)
Having gathered data from 341 participants (210 females and 131 males) over the age of 18, we investi-gated the predictive role of mindfulness, self-compassion, and caring for bliss in life satisfaction, controlled by perceived stress during the COVID-19 pandemic. The results of a confirmatory factor analysis acknowl-edged the single-factor structure of the Caring for Bliss Scale adapted within the scope of this study. The mean life satisfaction scores indicated that the sample was "displeased with the life" in the midst of the pandemic. In addition, the results of a hierarchical regression showed that, after controlling for perceived stress, mindfulness, caring for bliss, and self-compassion respectively explain a significant variance of life satisfaction scores during the COVID-19 pandemic. The hierarchical model proposed was found to account for 35% of variance in the life satisfaction levels of the participants across the relevant period. The results indicate that the Caring for Bliss Scale is a valid and reliable instrument to be used in Turkish culture. In ad-dition, mindfulness, self-compassion, and caring for bliss could be accepted as possible protective factors to be cultivated in order to enhance life satisfaction during the pandemic.
Keywords: Life Satisfaction; Mindfulness; Self-Compassion; Caring For Bliss; Perceived Stress; COVID-19